Manajemen Strategi Lembaga PAUD Menuju Akreditasi Di Kota Palopo - Pertiwi Kamariah Hasis; Arianti Raksa (UIN Sultan Maulana Hasanudin Banten, 2022)
This study aims to analyze the strategic management planning of PAUD institutions, analyze the implementation of PAUD institutions' strategic management, and analyze the results of the evaluation of PAUD's strategic management institutions. This study uses a qualitative descriptive method that is carried out by conducting a study in the field. The research was carried out in the Dian Gita Playgroup, Palopo City. Data collection techniques were carried out by interview, observation and documentation. The results of the study indicate that the strategy management process begins with conducting an environmental analysis or SWOT analysis. Through a SWOT analysis, it was found that the strengths of the Dian Gita Playgroup are located in densely populated areas, sources of funds, and facilities for playing and learning. The weakness is that the qualifications of educators do not meet, as well as the absence of educational staff. Opportunities are the support of parents of students, support from the central government and local governments, as well as a conducive school environment. While the challenge is that there are many other educational institutions around the school and people's thinking is still monotonous. Based on the results of the SWOT, planning is then carried out, namely: 1. The school leadership recruits educators with qualifications of having a D-II PGTK diploma from an accredited study program or having an S1 Early Childhood Education diploma. 2. The school leadership recruits education personnel with qualifications of having a minimum high school diploma (SMA) or having a bachelor's degree in Education Administration or Education Management. 3. Conduct curriculum reviews and improvements to the learning process that can support school accreditation. 4. Conducting socialization related to the importance of sending children to Early Childhood Education institutions before children enter the level of basic education. However, at the implementation stage, the Dian Gita Playgroup has not recruited educators and education personnel according to the qualifications required by BAN-PAUD. This is an obstacle in fulfilling one of the PAUD accreditation standards. As a result, there is 1 standard that does not meet the criteria, namely Standard 4, namely the Standard for Educators and Education Personnel. In the implementation stage, Dian Gita's playgroup has conducted a curriculum review and improvements to the learning process that can support school accreditation. 4. Conducting socialization related to the importance of sending children to Early Childhood Education institutions before children enter the level of basic education. As for the evaluation of the results of strategic management, it is necessary to recruit educators and education staff to meet the criteriabogv Standard. The Standard for Educators and Education Personnel.